Biosynthesis of azaphilones: a review. Issue 6 (2nd February 2021) - Pavesi, Coralie; Flon, Victor; Mann, Stéphane; Leleu, Stéphane; Prado, Soizic; Franck, Xavier
Abstract : Biosynthetic pathways for azaphilones are addressed from a genomic point of view. Abstract : Covering up to 2020 Azaphilones are fungal polyketide pigments bearing a highly oxygenated pyranoquinone bicyclic core; they are receiving a great deal of increasing research interest for their applications in the agroalimentary, dyeing, cosmetic, printing and pharmaceutical industries. Their biosynthetic pathways are not fully elucidated; however, thanks to recent genomic approaches combined with the increasing genome sequencing of fungi, some of these pathways have been recently unveiled. This is the first review on the biosynthesis of azaphilonoids adressed from a genomic point of view.